Antiepileptic Drugs in Children - Burçin Nazlı Karacabey; Edibe Pembegül Yıldız; Meliha Mine Çalışkan (Çocuk Dergisi)
Antiepileptic drugs (AEDs) lead to seizure freedom in about 70% of all children with epilepsy. Appropriate drug selection is determined by the patient’s age, seizure semiology, epileptic syndrome, and pharmacogenetic approach. The aim of treatment is to prevent seizures by maintaining the effective dose of one or more antiepileptic drugs. In recent years, many new generation AEDs with less side-effect profiles and drug interactions have been used in clinical practice. The clinical uses and side effects of AEDs are different in children than adults. The characteristics of AEDs in the pediatric age group are extremely important in the success of treatment. In this review, many current sources are examined, and the mechanisms of action, pharmacokinetic properties, clinical use and doses, side effects and drug interactions of AEDs that are frequently used in children are discussed.